Effects of Social Interactive - Constructivist Approach in Teaching Mathematics - Cañete, Rosemarie (IJRDO -JOURNAL OF MATHEMATICS, 2020)
This study aimed to determine the effectiveness of Social Interactive – Constructivist Approach in teaching Mathematics for Grade 10 learners in Dawis National High School (DNHS), Bayawan City for the School Year 2017 – 2018.The study made use of an experimental design particularly the Pre-Test and Post-Test Control Group Design wherein there were two groups of learners involved-the control groupand the experimental group. The study disclosed that both control and experimental groups got a failing rating in their pretest performance. After utilizing the conventional approach for the control group and social interactive-constructivist approach for the experimental group, the former group generally obtained a “fairly satisfactory” rating while the latter group, a “satisfactory” rating. Lastly, the use of the social interactive-constructivist approach is better than the conventional approach.